Identifikasi Prosedur Ekspor Benih Melon (Cucumis Melo L.) ke Negara Jepang (Studi Kasus di CV Multi Global Agrindo, Karanganyar): Penelitian - Fera Yuniarti Manurung; Ananti Yekti; Mastur (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The growth of a country's economy can be increased through the international trade sector, especially in export activities. Export activities often face problems such as long licensing processes, many requirements because the destination countries have different regulations. This study aims to identify the export procedures for melon seeds (Cucumis melo L.) to Japan Case Study at CV Multi Global Agrindo, Karanganyar. The type of research is a qualitative approach. The method used is through in-depth interviews with representative managers of CV Multi Global Agrindo, quarantine officers, and PT. Monang Sianipar Abadi as a Customs Service Entrepreneur (PPJK). Data analysis techniques are carried out by collecting data, reducing or simplifying, presenting data, and making conclusions to obtain an outline of the information. The results of the study indicate that in carrying out melon seed export activities, CV Multi Global Agrindo goes through several stages, namely 1) correspondence, 2) making invoices and packing lists by the company, 3) submitting permits to the Ministry of Agriculture until the Release Permit (SIP) is issued, 4) submitting applications and checking seeds to the Indonesian Quarantine Agency, 5) making shipping instruction documents by the company, 6) the process of checking the completeness and making documents at PT. Monang Sianipar Abadi as a Customs Service Management Entrepreneur (PPJK), 7) checking and making documents by freight forwarding, and 8) the process of making documents, booking flights and handing over goods to the airline. Mandatory requirements that must be met by exporters when exporting melon seeds to Japan are to use a phytosanitary certificate. The company did not experience significant obstacles in export activities, because various requirements and procedures could still be anticipated and fulfilled through good cooperation and communication between the exporters and related parties